The FDI determinants for high-tech companies - Josh Kallmer (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
Technology firms often make their greatest contributions to markets without making significant physical investments or hiring many people. This Perspective argues that governments need to think more expansively about their investment policies, to recognize the importance of cross-border data flows and enable these firms to deliver the benefits they promise.
Keywords: 330